Frailty is associated with 90-day mortality in urgent thoracic surgery conditionsCentral MessagePerspective - Jacqueline Kloos, BA; Aria Bassiri, MD; Vanessa P. Ho, MD, MPH, PhD; Jillian Sinopoli, DO; Leonidas Tapias Vargas, MD; Philip A. Linden, MD; Christopher W. Towe, MD (JTCVS Open, 2024)
Objective: In patients undergoing elective thoracic surgery, frailty is associated with worse outcomes. However, the magnitude by which frailty influences outcomes of urgent thoracic surgery (UTS) is unknown. Methods: We identified patients admitted with a UTS condition from January to September 2017 in the National Readmissions Database. UTS conditions were classified as esophageal perforation, hemo/pneumothorax, rib fracture, and obstructed hiatal hernia. Outcome of interest was mortality within 90 days of index admission. Frailty score was calculated using a deficit accumulation method. Cox proportional hazard modeling was used to calculate a hazard ratio for each combination of UTS disease type and frailty score, adjusted for sex, insurance payor, hospital size, and hospital and patient location, and was compared with the effect of frailty on elective lung lobectomy. Results: We identified 107,487 patients with a UTS condition. Among UTS conditions overall, increasing frailty elements were associated with increased mortality (hazard ratio, 2270; 95% CI, 1463-3523; P < .001). Compared with patients without frailty undergoing elective lobectomy, increasing frailty demonstrated trending toward increased mortality in all diagnoses. The magnitude of the effect of frailty on 90-day mortality differed depending on the disease and level of frailty. Conclusions: The effect of frailty on 90-day mortality after admission for urgent thoracic surgery conditions varies by disease type and level of frailty. Among UTS disease types, increasing frailty was associated with a higher 90-day risk of mortality. These findings suggest a valuable role for frailty evaluation in both clinical settings and administrative data for risk assessment.